The spatiotemporal variation and control mechanism of surface pCO2 in winter in Jiaozhou Bay, China. (13th December 2020) - Li, Yunxiao; Yang, Hong; Zhang, Longjun; Yang, Xufeng; Zang, Han; Fan, Wenhua; Wang, Gailing
Abstract: In many mid-latitude coastal waters during winter months, in addition to temperature, the large change in biogeochemical processes often influence and complicate the surface partial pressure of CO2 ( p CO2 ). Based on the hydrological and carbonate parameters in seven cruises, this study analysed the evolution process and explored the control mechanism of the surface p CO2 in Jiaozhou Bay, China, from December to March. The results showed that the p CO2 ranged from 157 μatm to 647 μatm, and the bay represented a sink for atmospheric CO2 (−4.02 mmol m −2 d −1 ) in the whole winter. The non-temperature processes were the dominant factors affecting intra-winter p CO2 variation. In December, the bay was dominated by aerobic respiration and acted as a CO2 source (1.61 mmol m −2 d −1 ). From early January to late February, however, the vigorous growth of cold algae caused strong primary production, and the bay presented as a CO2 sink (from −3.68 mmol m −2 d −1 in early January to −10.82 mmol m −2 d −1 in late February). In March, primary production weakened and the effects of the CaCO3 precipitation appeared, and the strength of the CO2 sink was obviously weakened (−1.72 mmol m −2 d −1 ). Meanwhile, the water temperature decreased gradually from December to late January and then increased until March, and it further expanded the variation range of p CO2 . Our results highlight the obvious source/sink change in mid-latitude seawater CO2 in winter, while more field observations are still needed to further understand the complicated biogeochemical processes and its influence on seawater p CO2 . Highlights: Strong biogeochemical process showed in some mid-latitude coastal seas in winter. Detailed variation in CO2 behavior in Jiaozhou Bay in winter were investigated. Underlying processes controlling seawater CO2 variation was revealed. Biogeochemical process affecting seawater CO2 differed in various period.